Campaña de comunicación sobre el maltrato masculino en la sociedad quiteña. Piloto en la asociación papá por siempre. - Holguín Mendoza, Sonia Alexandra (2014)
The domestic violence that exists in our country is an evident social problem that affects men as much as women. However, the issue of masculine domestic abuse has not been treated with the same importance as female domestic abuse, as in Ecuador, the image of a man being abused is almost unthinkable. It is known that the family is the birthplace of learned and developed emotions and attitudes in persons, differentiating historically the gender hierarchies; which makes a previous investigation indispensible, and to work together with men, fathers within the association of: “Papá Por Siempre”, where they practice the foundation of the theory of functionalism, because it is important to know and explain the reality of the subject, the social problem, and the possible causes and effects.